Isu Kontemporer Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah: Contemporary Issues in Arabic Language Learning in Elementary Islamic Schools - Kamila, Farichatul; Aisa, Firda; Susilawati, Sinta Ayu; Abu Bakar, M. Yunus (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2023)
The purpose of Arabic language learning in elementary Islamic schools has not yet achieved the intended goals, which include the four language skills: speaking, reading, listening, and writing. Based on the results of a field survey at Wahid Hasyim Elementary Islamic School in Yogyakarta, the purpose of Arabic language learning only prioritizes two skills, namely speaking and listening, where students are required to communicate using Arabic. However, the other two skills are addressed. According to the author, the Arabic language material in elementary Islamic schools is not ideal because many materials are taught in a sequence of straightforward, complex, moderate, challenging, and accessible, complicating students' receiving the prepared material. In contrast, the material should ideally start from easy, medium, and then hard to facilitate students' learning. In Arabic language learning in elementary Islamic schools, the